2020
DOI: 10.1136/ijgc-2020-001716
|View full text |Cite
|
Sign up to set email alerts
|

Fertility sparing surgery for patients with FIGO stage I clear cell ovarian carcinoma: a database analysis and systematic review of the literature

Abstract: ObjectiveFertility sparing surgery for patients with early stage ovarian clear cell carcinoma is controversial. We aimed to investigate the impact of fertility sparing surgery on the oncologic outcomes of young patients with stage I ovarian clear cell carcinoma.MethodsThe National Cancer Database was accessed and patients with pathological stage IA or IC ovarian clear cell carcinoma, aged <45 years, were selected. Based on site specific surgery codes, patients who underwent fertility sparing or radical surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Large retrospective studies and metaanalyses have found that for stage I epithelial ovarian cancer, fertility-sparing surgery did not appear to compromise disease-free survival (DFS) or overall survival (OS) compared with radical surgery. [76][77][78][79][80][81][82][83][84][85] Although clear cell histology is associated with increased risk of poor outcomes, 83 some studies have shown that even among patients with stage I clear cell, fertility-sparing surgery does not increase risk of relapse or shorten survival compared with radical surgery. 77,78,81,82,85 Large retrospective studies among patients with stage I borderline ovarian tumors have found that recurrence rate and survival is similar for those treated with fertility sparing versus radical surgery.…”
Section: Fertility Sparing Options For Stage I Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Large retrospective studies and metaanalyses have found that for stage I epithelial ovarian cancer, fertility-sparing surgery did not appear to compromise disease-free survival (DFS) or overall survival (OS) compared with radical surgery. [76][77][78][79][80][81][82][83][84][85] Although clear cell histology is associated with increased risk of poor outcomes, 83 some studies have shown that even among patients with stage I clear cell, fertility-sparing surgery does not increase risk of relapse or shorten survival compared with radical surgery. 77,78,81,82,85 Large retrospective studies among patients with stage I borderline ovarian tumors have found that recurrence rate and survival is similar for those treated with fertility sparing versus radical surgery.…”
Section: Fertility Sparing Options For Stage I Diseasementioning
confidence: 99%
“…[76][77][78][79][80][81][82][83][84][85] Although clear cell histology is associated with increased risk of poor outcomes, 83 some studies have shown that even among patients with stage I clear cell, fertility-sparing surgery does not increase risk of relapse or shorten survival compared with radical surgery. 77,78,81,82,85 Large retrospective studies among patients with stage I borderline ovarian tumors have found that recurrence rate and survival is similar for those treated with fertility sparing versus radical surgery. [86][87][88][89] In retrospective studies, including multivariate analyses, fertility sparing surgery does not appear to be associated with poorer outcomes (DFS, PFS, OS) compared with more extensive surgery in patients with stage I germ cell tumors and sex-cord stromal tumors.…”
Section: Fertility Sparing Options For Stage I Diseasementioning
confidence: 99%
“…Because OCCC is mostly a tumor with poor pathological differentiation, some studies have pointed out the controversy of FSS in OCCC patients [20], while others have suggested that compared with FSS and radical surgery, there is no difference in OS between the two groups of patients, after adjusting for lymph node resection. Moreover, disease staging or FSS did not affect OS [21]. In our survival curve, we can see that the prognosis of patients who underwent intermediate and advanced tumor debulking surgery was signi cantly worse, while there seemed to be no signi cant difference between patients who underwent FSS and complete hysterectomy and bilateral adnexa, as the choice of surgical method was also closely related to disease stage.…”
Section: Discussionmentioning
confidence: 65%
“…We report on nine patients who underwent fertility conservation, none of whom experienced recurrent disease after a median follow-up of 95.4 months. The literature is limited with regard to fertility conservation in this patient population: a National Cancer Database analysis of 33 women with stage IA and 24 women with stage IC ovarian clear cell carcinoma found no difference in survival between patients undergoing fertility-sparing surgery versus radical cytoreduction, although lymphadenectomy was deferred in nearly half of the cases 22. A systematic review of 132 patients with stage IA/IC disease undergoing fertility-sparing surgery reported a 15% relapse rate; however, the analysis did not account for whether patients were fully staged 22.…”
Section: Discussionmentioning
confidence: 99%